(untitled) (Journal of Health Sciences, 2018)
Introduction: The aim of this study was to assess effects of strength, stretching and balance home exercise program (moderate intensity, performed once a day, five times a week) on quality of life of people with knee osteoarthritis. Methods: Participants with knee osteoarthritis performed physical therapy for a period of two weeks at the Department for Physical Medicine and Rehabilitation. The study group (n=30) continued to perform exercise program at home while the control group (n=30) did not continue the exercise program. The participants in the study group performed strength, stretching and balance exercises of moderate intensity, once a day, five times a week, for a total of eight weeks. The Short Form-36 Health Questionnaire (SF-36) was used to examine the effects of exercise program. Results: There was no the difference between the average value of quality of life in all examined areas (physical functioning, role limitations due to physical problems, role limitations due to emotional problems, vitality/energy, mental health, social functioning, physical pain, perception of general health) at the beginning of the study between the study group and control group (p>0.05 in all eight areas). The difference between the average value of quality of life at the beginning and end of the study was statistically significantly higher in the study group compared to the control group (physical functioning p=0.0001; role limitations due to physical problems p=0.0001; role limitations due to emotional problems p=0.0001; vitality/energy p=0.0001; mental health p=0.0001; social functioning p=0.0001; bodily pain p=0.0001; perception of general health p=0.0001). Conclusion: Home exercise program consisting of strength, stretching and balance exercises, of moderate intensity, performed once a day, five times a week is effective in improving quality of life of people with knee osteoarthritis.